Specification and refinement of finite dataflow networks a relational approach - Broy, Manfred 1949-; Stølen, Ketil (1994)
Abstract: "We specify the black box behavior of dataflow components by characterizing the relation between the input and the output histories. We distinguish between three main classes of such specifications, namely time independent specifications, weakly time dependent specifications and strongly time dependent specifications. Dataflow components are semantically modeled by sets of timed stream processing functions. Specifications describe such sets by logical formulas. We emphasize the treatment of the well-known fair merge problem and the Brock/Ackermann anomaly. We give refinement rules which allow specifications to be decomposed into networks of specifications."
Keywords: Computer programming; Data flow computing; Discrete-time systems; Parallelverarbeitung; Forschungsbericht